Changes in Non-Structural Carbohydrates, Wood Properties and Essential Oil During Chemically-Induced Heartwood Formation in Dalbergia odorifera - Cui, Zhiyi; Li, Xiaofei; Xu, Daping; Yang, Zengjiang (Frontiers in Plant Science, 2020)
The highly valuable heartwood of Dalbergia odorifera, named “Jiang Xiang” in traditional Chinese medicine, forms very slowly, thus, study on the rapid promotion of “Jiang Xiang” production in Dalbergia odorifera is encouraged. However, no effective methods are available that can be applied in practice and little is known about the physiological changes in xylem during artificially induced heartwood production. Chemical induction is considered to be one of the most promising methods of inducing heartwood formation in other tree species. Therefore, three potential induction candidates: acetic acid, sodium chloride and hydrogen peroxide solutions were injected into the trunk, and their induction effects and changes in physiological parameters related to heartwood formation such as non-structural carbohydrates, lipids, wood properties and essential oil during the induction process were investigated. Similar to the formation of natural heartwood, chemical-induced “Jiang Xiang” production was accompanied by sapwood dehydration, non-structural carbohydrates consumption and synthesis of heartwood substances. As the heartwood substances accumulated, the density and essential oil content increased gradually, thereby “Jiang Xiang” was finally produced. In this process, physiological parameters of discolored sapwood gradually evolved to resemble those of natural heartwood. Hydrogen peroxide-induced “Jiang Xiang” was closest to natural heartwood and the essential oil components met the required standards of high-quality “Jiang Xiang”; however the induction effects of acetic acid and sodium chloride were poor. Thus, hydrogen peroxide has potential to induce “Jiang Xiang” production in Dalbergia odorifera and hydrogen peroxide-induced production of “Jiang Xiang” has strong market potential.